Free fertilizer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The World Bank is funding a project in Kenya to distribute fertilizer in two kilogram bags in the hope that this will boost fertilizer use on smallholder farms. This pilot project is being conducted in the province of Kisii (near Lake Victoria)...